Accuracy of static computer-aided assisted implant surgery (s-cais) using surgical guide fabricated from different 3D printing technologies - Bathija, Anshu. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Posthodontics.; Advisor: Andre DeSouza.; Committee: Matthew Finkelman, Kiho Kang, YongJeong Kim, and Panos Papaspyridakos.; Keyword: Dentistry.